2018
DOI: 10.21037/qims.2018.03.08
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and imaging features of pituitary apoplexy and role of imaging in differentiation of clinical mimics

Abstract: To discuss the clinical syndrome, review common imaging findings of pituitary apoplexy (PA) and role of imaging in therapy and follow-up. Also, to review other acute clinical scenarios with similar clinical and/or imaging findings as PA. PA is a severe and potentially life-threatening medical emergency, characterized by constellation of symptoms/signs that occur as a result of acute hemorrhage and/or infarction in pituitary gland. Patients present with acute and sudden onset of symptoms/signs, most commonly wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
54
0
10

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(65 citation statements)
references
References 58 publications
1
54
0
10
Order By: Relevance
“…Most emergency departments use standard blood test screens at admission, and cerebral CT-scans are also widely used in this setting. Studies have shown that CT only detects 21% of PA, whereas 90% is visualized with MRI [12, 21]. The absence of visual impairment and lack of clear anterior pituitary affection undoubtedly delayed the MRI and hence the final diagnosis in our case.…”
Section: Discussionmentioning
confidence: 78%
“…Most emergency departments use standard blood test screens at admission, and cerebral CT-scans are also widely used in this setting. Studies have shown that CT only detects 21% of PA, whereas 90% is visualized with MRI [12, 21]. The absence of visual impairment and lack of clear anterior pituitary affection undoubtedly delayed the MRI and hence the final diagnosis in our case.…”
Section: Discussionmentioning
confidence: 78%
“…In addition, the diagnosis of PA may be missed as its clinical presentation can be acute or subacute with symptom presentation being dependent on the extent of bleeding and edema extension. 4 There are numerous types of pituitary tumors that are known to be associated with PA but the most common types are chromophobe adenomas followed by eosinophilic adenomas; most tumor types associated with PA have been found to be endocrinologically significant. 5 Corticotropic deficiency is the most common endocrinologic deficit in PA, followed by thyrotropic and gonadotropic deficiency.…”
Section: Discussionmentioning
confidence: 99%
“…In this report, we present a 70-year-old man who developed a right oculomotor nerve palsy secondary to apoplexy within a pituitary adenoma, missed on initial CT, further emphasizing the limitations of CT in diagnosing sellar lesions and specifically PA. MRI brain is therefore the favored mode of imaging for cases with a high degree of suspicion for PA. 4 A key take-home point is maintaining a high degree of suspicion given a new-onset headache accompanied by neurologic findings. Despite a CT scan that was initially reported as unremarkable, our high index of suspicion led us to review the CT images in more detail to assist us in eliciting the diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…2 b) and sagittal ( Fig. 2 c) images causing mild compression on the optic chiasm, which is suggestive of acute pituitary apoplexy [8]. Thus, the patient was emergently managed for both pituitary apoplexy and pulmonary infection and was treated by hormone replacement therapy (adrenocortical hormone and levothyroxine sodium tablets), antibiotics (moxifloxacin and ganciclovir), ambroxol, and doxofylline.…”
Section: Case Presentationmentioning
confidence: 99%